PENGARUH LAMA PENYIMPANAN DAN JUMLAH MATA TUNAS BATANG ATAS TERHADAP KEBERHASILAN SAMBUNG PUCUK ALPUKAT (Persea americana Mill.) - Auliyana, Fadhila; Murrinie, Endang Dewi; Suharijanto, Suharijanto (Universitas Muria Kudus, 2022)
Avocado plants (Persea americana Mill.) can be propagated vegetatively through grafting. One of the main problems in grafting is the decline in the quality of the scion during storage if it must be imported from other areas, thereby reducing the success of grafting. Another factor that must be considered in grafting is the number of buds, the more the number of buds used, the more shoots that grow. The purpose of the study was to determine the effect of storage time and the number of scion buds on the success of grafting avocado shoots. The research was conducted from March to June 2022 at the Bulu Horticultural Seed Garden, Bulu District, Rembang Regency, Central Java. The study was a two-factor factorial experiment using a completely randomized block design which was repeated three times. The first factor was the storage time of the scion which consisted of three levels, namely 0, 3, and 6 days. The second factor is the number of buds, consisting of 3 levels, namely 2, 3, and 4 buds. The results showed that storage time had no effect on the success of grafting avocado shoots. However, 6 days of storage gave the lowest number of leaves at the age of 6 weeks after grafting. The number of buds did not affect the success of grafting avocado shoots. There was no interaction between storage time and the number of buds on the success of grafting avocado shoots.